TRANSFORMASI KABUPATEN CILACAP MENUJU WILAYAH BERKARAKTER NEGARA KELAUTAN - Susdarwono, Endro Tri; Aminullah , Faujan (Jurnal Inovasi Daerah, 2023)
This research was conducted to contribute ideas regarding maritime countries. How regions within a maritime state must implement certain instruments in order to be said to be part of a maritime state. This research aims to provide a description of the transformation of Cilacap district into a region based on its character as a maritime country. The type of research used is descriptive qualitative with the type of data including secondary data and the collection technique used is library research. The data analysis technique used is the qualitative content analysis data analysis technique, namely which is the author analyzes secondary data, then uses theory to explain a phenomenon or event that the author is researching. This research concludes that based on six important sources of instruments related to transformation into a region that has the character of being part of a maritime country, Cilacap, with its potential and optimal utilization, has taken steps to become a region that has a maritime character. This research recommends that more in-depth research can be carried out regarding areas that actually already have potential or have implemented certain instruments as part of a maritime country.